Konsep Keluhuran Seorang Imam Menurut John Chrysostom - Seniman Gulo; Hendi Hendi (Sekolah Tinggi Teologi Berita Hidup, 2021)
The nobility of the priest is to be Christ's sole representative on earth and to mediate between God and men. The nobility of a priest is not just an office or an ordinary position, but the priest is a noble job that people do not have. Through literature research from John Chrysostom there are two important points in the nobility of the priest. First, what is the nobility of the priest, Second, discuss the role of the pastor in the spirituality of the congregation. The nobility of the priest ultimately leads man to experience or unite with the Triune God.Keluhuran imam adalah menjadi wakil Kristus satu-satunya di bumi dan menjadi pengantara Allah dan manusia. Keluhuran seorang imam bukan hanya jabatan atau kedudukan yang biasa-biasa saja namun imam adalah suatu pekerjaan yang mulia yang orang tidak miliki. Melalui penelitian literatur dari John Chrysostom ada dua pokok penting dalam keluhuran imam. Pertama, apa itu keluhuran imam, Kedua, mendiskusikan peranan gembala dalam kerohanian jemaat. Keluhuran imam pada akhirnya membawa manusia untuk mengalami atau menyatu dengan Allah Tritunggal.